The Effect of Interest Rates and Inflation on Economic Growth in ASEAN-5 Countries - Purnomo, Dewi Karina; Wibowo, Wisnu (Journal of Developing Economies, 2024)
This study aims to empirically test the effect of interest rates and inflation on economic growth, with gross capital formation as a control variable. This research uses panel data from 5 ASEAN countries, namely Indonesia, Malaysia, the Philippines, Singapore, and Thailand in 2004 – 2021 and was tested using the Random Effect Model (REM) analysis technique. The results of this study explain that interest rates and inflation have a simultaneous effect on economic growth. Another finding from this study is that interest rates have a significantly negative effect on economic growth and inflation has a significant positive effect on economic growth. However, this study is subject to several limitations. First, it solely focuses on ASEAN-5 countries, thus limiting the generalizability of the findings to other developed and developing nations. Second, the study’s reliance on annual data from 2004 to 2021 excludes more recent data, potentially overlooking current economic trends. Third, the static panel method utilized with the REM analysis only provides a broad overview of the relationships between interest rates, inflation, and economic growth, lacking deeper insights into long-term and short-term dynamics. Fourth, while the study covers the period including the COVID-19 pandemic, it fails to thoroughly explore its impact and provide detailed explanations. Thus, future research should consider expanding the scope beyond ASEAN-5, incorporating more recent data, employing dynamic panel methods, and thoroughly investigating the implications of significant events such as the COVID-19 pandemic on the examined relationships.